Public policy lessons from the AIDS response in Africa - (:unkn) unknown (My University, 2021)
Public Policy Lessons from the AIDS Response in Africa examines how the interplay between national state dynamics in Africa and the global political arena has shaped the global AIDS response, and in this context develops a framework for analysing public policy action more broadly in contemporary Africa. By applying comparative political sociology to AIDS public action, this book identifies four political models that are applicable to public initiatives. Fred Eboko goes on to test these in other domains - namely, the malaria and tuberculosis health subsectors, and the education and environment sectors. By articulating global and national connections and contributing a critical perspective grounded in African scholarship and French political science, the author builds a bold and ambitious framework with the potential to enable coherent and effective public policy action in Africa. This book will be of interest to scholars and students of public health, global health, political science, and development studies, as well as policy-level practitioners in the areas of global health and development.
Keywords: African Research